PENGUATAN PERAN GURU BK DENGAN IMPLEMENTASI DEEP LEARNING - Dwi Setyoningsih, Yunita (Al-Umron : Jurnal Pengabdian Kepada Masyarakat, 2025)
Generation Z and Alpha students face complex developmental challenges in the digital era, including moral degradation and increasing individualism driven by social media. These conditions require school counselors to adapt their services to align with the unique characteristics of these generations. Deep learning, as promoted in the Merdeka Curriculum, offers a relevant approach; however, school counselors' understanding of this concept and its practical application remains limited. This community service program aimed to enhance the understanding of deep learning-based guidance and counseling services among high school counselors in the MGBK (School Counselors’ Association) of Kudus Regency. The activity involved 70 school counselors and employed a Participatory Action Research (PAR) approach over two weeks, consisting of five phases: (1) Diagnosing, identifying the core issues—difficulties in analyzing students’ needs and limited understanding of deep learning; (2) Action Planning, designing interventions through seminars, lectures, demonstrations, and online mentoring; (3) Action Taking, conducting training sessions with expert speakers; (4) Evaluating, assessing the intervention’s impact using open-ended questionnaires; and (5) Specifying Learning, documenting lessons learned from successes and challenges. The results showed a significant increase in counselors’ understanding, with average scores improving from 4.28 to 5.42. These findings indicate that the deep learning approach can be effectively integrated into school counseling practices through contextual and collaborative professional development programs.